Associations between Extracellular Matrix Protein 1 Gene Polymorphism and Progression of Liver Disease - Xiuting He; Ting Liu; Rui Zhang; Xu Li (Genetics Research)
Background. Our study aimed to investigate the relationship between extracellular matrix 1 (ECM1) gene polymorphism and progression of liver fibrosis in the Chinese population. Methods. A total 656 patients with hepatitis B virus (HBV) infection and 298 healthy individuals of the Chinese Han population were recruited for a retrospective case-control study. Of the disease group, 104 cases had chronic hepatitis B (CHB), 266 had LC, and 286 had hepatocellular carcinoma (HCC). Subjects were frequency-matched according to age and gender. Polymorphisms of the ECM1 gene were examined using the MassARRAY SNP genotyping method. Results. There were no associations between genotype and allele frequencies of ECM1 rs3737240 and rs13294 loci with the risk of CHB and CHB-related HCC. After adjustment for age, sex, smoking status, and drinking habits, the GT genotype was dramatically related to a reduced risk of chronic HBV infection in both non-HCC (OR = 0.68, 95% CI: 0.49-0.94) and total chronic HBV infection patients (OR = 0.75, 95% CI: 0.56-1.00). Haplotype analyses revealed twelve protective haplotypes against total chronic HBV infection and four against non-HCC chronic HBV infection. Conclusion. ECM1 gene polymorphism in rs3834087 and rs3754217 loci is associated with a reduced risk of chronic HBV infection but not with liver fibrosis development and the occurrence of HCC.